Chlamydia trachomatis dapF Encodes a Bifunctional Enzyme Capable of Both d-Glutamate Racemase and Diaminopimelate Epimerase Activities - George Liechti (American Society for Microbiology, 2018)
ABSTRACT Peptidoglycan is a sugar/amino acid polymer unique to bacteria and essential for division and cell shape maintenance. The d-amino acids that make up its cross-linked stem peptides are not abundant in nature and must be synthesized by bacteria de novo. d-Glutamate is present at the second position of the pentapeptide stem and is strictly conserved in all bacterial species. In Gram-negative bacteria, d-glutamate is generated via the racemization of l-glutamate by glutamate racemase (MurI). Chlamydia trachomatis is the leading cause of infectious blindness and sexually transmitted bacterial infections worldwide. While its genome encodes a majority of the enzymes involved in peptidoglycan synthesis, no murI homologue has ever been annotated. Recent studies have revealed the presence of peptidoglycan in C. trachomatis and confirmed that its pentapeptide includes d-glutamate. In this study, we show that C. trachomatis synthesizes d-glutamate by utilizing a novel, bifunctional homologue of diaminopimelate epimerase (DapF). DapF catalyzes the final step in the synthesis of meso-diaminopimelate, another amino acid unique to peptidoglycan. Genetic complementation of an Escherichia coli murI mutant demonstrated that Chlamydia DapF can generate d-glutamate. Biochemical analysis showed robust activity, but unlike canonical glutamate racemases, activity was dependent on the cofactor pyridoxal phosphate. Genetic complementation, enzymatic characterization, and bioinformatic analyses indicate that chlamydial DapF shares characteristics with other promiscuous/primordial enzymes, presenting a potential mechanism for d-glutamate synthesis not only in Chlamydia but also numerous other genera within the Planctomycetes-Verrucomicrobiae-Chlamydiae superphylum that lack recognized glutamate racemases. IMPORTANCE Here we describe one of the last remaining “missing” steps in peptidoglycan synthesis in pathogenic Chlamydia species, the synthesis of d-glutamate. We have determined that the diaminopimelate epimerase (DapF) encoded by Chlamydia trachomatis is capable of carrying out both the epimerization of DAP and the pyridoxal phosphate-dependent racemization of glutamate. Enzyme promiscuity is thought to be the hallmark of early microbial life on this planet, and there is currently an active debate as to whether “moonlighting enzymes” represent primordial evolutionary relics or are a product of more recent reductionist evolutionary pressures. Given the large number of Chlamydia species (as well as members of the Planctomycetes-Verrucomicrobiae-Chlamydiae superphylum) that possess DapF but lack homologues of MurI, it is likely that DapF is a primordial isomerase that functions as both racemase and epimerase in these organisms, suggesting that specialized d-glutamate racemase enzymes never evolved in these microbes.